Application of the Homotopy Analysis Method for Solving the Systems of Linear and Nonlinear Integral Equations - Brociek, Rafal; Hetmaniok, Edyta; Matlak, Jaros law; Slota, Damian (Mathematical Modelling and Analysis, 2016)
In this paper we indicate some applications of homotopy analysis method for solving the systems of linear and nonlinear integral equations. The method is based on the concept of creating function series. If the series converges, its sum is the solution of this system of equations. The paper presents conditions to ensure the convergence of this series and estimation of the error of approximate solution obtained when the partial sum of the series is used. Application of the method will be illustrated by examples.